Improving Interpersonal Communication Skills through Group Guidance with Assertive Training Techniques - Shintia Dwi Putri; Marjohan Marjohan; Firman Firman; Dina Sukma (Yayasan Keluarga Guru Mandiri, 2023)
This study aims to demonstrate the effectiveness of group mentoring services utilizing assertive training techniques in enhancing the interpersonal communication skills of students. A quasi-experimental design was employed, with a sample of twenty students from a public junior high school in Indonesia, evenly divided into experimental and control groups using probability sampling with simple random sampling techniques. Interpersonal communication skills were assessed using instruments developed by the researchers and evaluated by experts. Data analysis involved the Wilcoxon signed-rank test and Kolmogorov-Smirnov. The results indicate a significant increase in the interpersonal communication skills of the experimental group students, with their average scores increasing from 67.2 before receiving group counseling services to 123 after implementing assertive training techniques. In contrast, the control group's average scores increased from 87.1 to 105.6 after the same intervention. This study highlights the effectiveness of group mentoring with assertive training techniques in enhancing students’ interpersonal communication skills, contributing valuable insights to the field of educational psychology and counseling.